Generated significant environmental impacts for the activities of the laboratory of the ministry of transports and communications - Nieto Farina, Florencia Esther (2012)
The present work allows to identify and to know the signifi cant environmental impacts generated by the laboratory activities developed in the Department of Laboratory of the Offi ce of Technological Support of the Ministry of Transports and Communications; through the description of the processes and activities developed in seven (07) units (areas) of laboratory that they conform it; the identifi cation of the signifi cant environmental aspects associated to the processes and activities of each unit and the hierarchization of the signifi cant environmental impacts, to this way to select y/o to propose measures of control y/o minimización of the identifi ed impacts as significant.